Edição e estudo de atas mato-grossenses do século XIX : Irmandade da Nossa Senhora da Conceição - Lé, Laura Aristimunha da Silva (2023)
This dissertation deals with the Brotherhood of Nossa Senhora da Conceição in Cuiabá, Brazil, as a relevant historical and cultural phenomenon for understanding social, religious and gender dynamics from 1895 to 1898. The main objective of this study is to analyse the acts of the Brotherhood of Nossa Senhora da Conceição, to uncover the gender representations, present in the documents, and to explore the historical and social context in which this Brotherhood developed. This research uses a philological approach, including a detailed textual analysis of twenty of the Brotherhood's acts from 1895 to 1898. In addition, other sciences that work in partnership with philology, such as paleography, codicology and diplomatic, are explored to understand not only the writing and language of the acts, but also the material, formal and writing elements of the period of the historical manuscripts. The results of the research revealed important aspects of the history of the Brotherhood of Nossa Senhora da Conceição, including the socio-historical context of Cuiabá and the role of the Brotherhoods in the cultural and religious construction of the region. The philological work, using facsimile and semi-diplomatic editions of the acts, has led to a linguistic and historical understanding that has contributed to the knowledge and appreciation of the Brotherhood's cultural heritage. In addition, the analysis of the acts provides information on the gender dynamics in the Brotherhood and how women played a significant role in this context. This dissertation, within the field of philology and history, proved to be an opportunity to get to know the selected acts, as well as to use other sciences in the process of interpreting and understanding the records inserted in these acts. Overall, this study enriches our understanding of local history and makes a significant contribution to our knowledge of the history of the Portuguese language.